(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article discusses the use of research methods in teaching and the fact that they are part of different pedagogical concepts of education and upbringing. In addition, the formation of research skills by students through the teaching of general subjects, certain features of the generality of problem-based and research-based teaching methods, the commonality between research, heuristic and problem-based teaching methods were discussed and demonstrated